Criminal justice involvement history is associated with better HIV care continuum metrics among a population-based sample of young black MSM. (2nd January 2017) - Schneider, John A.; Kozloski, Michael; Michaels, Stuart; Skaathun, Britt; Voisin, Dexter; Lancki, Nicola; Morgan, Ethan; Khanna, Aditya; Green, Keith; Coombs, Robert W.; Friedman, Samuel R.; Laumann, Edward; et al.
Abstract : Objective: To examine how history of criminal justice involvement (CJI) is related to HIV care continuum metrics among young black MSM 16–29 years of age. Design: Population-based survey. Methods: From 2013 to 2014, a representative sample of young black MSM was generated using respondent-driven sampling (RDS) in Chicago ( n = 618). HIV antibody/antigen and RNA testing were performed using dry blood spots. Factors assessed in the care continuum included HIV testing, HIV diagnosis, linkage to care within 6 months, retention in care, adherence to antiretrovirals, and viral suppression. RDS-weighted regression models examined the associations between history of CJI, including frequency of CJI and durations of stay and each of the continuum metrics. Results: A final analytic sample of 618 participants was generated through RDS chains of up to 13 waves in length and with a mean of 2.1 recruits per participant. At enrollment, 40.8% had prior history of CJI and 34.6% were HIV seropositive. Of persons reporting HIV seropositive status, 58.4% were linked to care, 40.2% were retained in care, 32.2% were adherent to antiretrovirals, and 24.3% were virally suppressed. Any CJI history was associated with the overall care continuum (adjusted odds ratio = 2.35; 95% confidence interval 1.13–4.88) and was most associated with increased retention in care [adjusted odds ratio = 3.72 (1.77–7.84)]. Having one CJI experience and detention for only 1 day was associated with better retention in care compared with no or more frequent CJI. Conclusion: Those with a previous history of CJI were more successful in achieving most HIV care continuum metrics. Frequent and cycling CJI, however, was detrimental to HIV care. Abstract : Supplemental Digital Content is available in the text